Antimicrobial peptides and bacteriocins: alternatives to traditional antibiotics - Sang, Yongming; Blecha, Frank (My University, 2013)
Antimicrobial peptides (AMPs) are ubiquitous, gene-encoded natural antibiotics that have gained recent attention in the search for new antimicrobials to combat infectious disease. In multicellular organisms, AMPs, such as defensins and cathelicidins, provide a coordinated protective response against infection and are a principal component of innate immunity in vertebrates. In unicellular organisms, AMPs, such as bacteriocins, function to suppress competitor species. Because many AMPs kill bacteria by disruption of membrane integrity and are thus thought to be less likely to induce resistance, AMPs are being extensively evaluated as novel antimicrobial drugs. This review summarizes and discusses the antibiotic properties of AMPs highlighting their potential as alternatives to conventional antibiotics.
Keywords: Antibiotics; Antimicrobial peptides; Bacteriocin; Animal health